Cylinder drag reduction using discrete surface roughness: An experimental investigation into the effect of cylindrical roughness elements - Deval, P. (2023)
This thesis investigates the influence of Cylindrical Distributed Roughness Elements (polka-dots) on cylinder flow, with a focus on potential applications in sports aerodynamics. The primary goals are twofold: to explore the mechanism behind tripping and to analyse how the dimensions (height, width, spacing) of polka-dots affect flow characteristics.